2020
DOI: 10.1007/s00216-020-03064-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenated high-resolution mass spectrometry—the “all-in-one” device in analytical toxicology?

Abstract: This trend article reviews papers with hyphenated high-resolution mass spectrometry (HRMS) approaches applied in analytical toxicology, particularly in clinical and forensic toxicology published since 2016 and referenced in PubMed. The article focuses on the question of whether HRMS has or will become the all-in-one device in these fields as supposed by the increasing number of HRMS presentations at scientific meetings, corresponding original papers, and review articles. Typical examples for the different appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…High-resolution MS devices allow the differentiation of isobaric compounds with the same nominal mass but different elemental compositions, but isomeric compounds can only be differentiated by fragmentation. 20 Further pitfalls in drug testing by hyphenated low-resolution and high-resolution MS have been described elsewhere. 19 Using bioanalytical methods, adherence can be assessed directly and objectively, 5 and it has been demonstrated that MS-based monitoring improves adherence.…”
Section: Resultsmentioning
confidence: 99%
“…High-resolution MS devices allow the differentiation of isobaric compounds with the same nominal mass but different elemental compositions, but isomeric compounds can only be differentiated by fragmentation. 20 Further pitfalls in drug testing by hyphenated low-resolution and high-resolution MS have been described elsewhere. 19 Using bioanalytical methods, adherence can be assessed directly and objectively, 5 and it has been demonstrated that MS-based monitoring improves adherence.…”
Section: Resultsmentioning
confidence: 99%
“…or in application notes from major instrument manufacturers. In contrast, with greater mass resolution and accuracy, HRMS‐based screening approaches can cover thousands of drugs in a single analytical run, which is advantageous in STA 10,14,21 . Most common HRMS instruments are of the time‐of‐flight (TOF) or orbitrap types with compound libraries used for data interpretation 10 .…”
Section: A Brief Overview Of Commonly Applied Sta Methods In Forensic...mentioning
confidence: 99%
“…In the past decades, immunoassays, gas chromatography (GC), liquid chromatography (LC), and other chromatographic methods using various detectors, such as UV‐diode array detection, have commonly been used in STA 3,8 . More recently, there has been an increase in the application of hyphenated chromatographic and spectrometric methods, such as LC–tandem mass spectrometry (LC–MS/MS), GC–MS/MS, and highly selective and sensitive screening procedures using LC–high‐resolution MS (LC–HRMS) 9,10 . Despite the comprehensive description and review of the numerous methods employed for STA, the overall STA strategy comprising an overview of the method setups used for STA in the individual laboratories has been less commonly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical toxicology (CT) and forensic toxicology (FT) represent two disciplines of toxicology dedicated to the qualitative and quantitative analysis and respective interpretation of alcohol, drugs of abuse (DOA), prescription drugs, or poisons, mainly in humans. Analytically, both apply similar techniques beginning with simple urine immunoassay (IA) prescreening procedures, followed or complemented with highly sophisticated confirmatory or general unknown screening (GUS) hyphenated chromatographic techniques; for example, gas chromatography (GC)-mass spectrometry (MS) or liquid chromatography (LC)-MS either in low or high resolution (HR; Drummer, 2007;Maurer, 2010Maurer, , 2021Meyer et al, 2014;Peters, 2011). Quantification of positive screening results in the blood is performed to assess the extent of exposure, the risk for drug side effects and complications, or the degree of impairment of toxicologically relevant compounds.…”
Section: Clinical and Forensic Toxicologymentioning
confidence: 99%